Validity of the Iwate criteria for patients with hepatocellular carcinoma undergoing minimally invasive liver resection. (6th September 2018) - Krenzien, Felix; Wabitsch, Simon; Haber, Philipp; Kamali, Can; Brunnbauer, Philipp; Benzing, Christian; Atanasov, Georgi; Wakabayashi, Go; Öllinger, Robert; Pratschke, Johann; Schmelzle, Moritz
Abstract: Background: Recently proposed by the International Consensus Conference on Laparoscopic Liver Resection, the Iwate criteria (IC) can be used by surgeons to predict the operative difficulty of laparoscopic liver resection (LLR) and were validated in patients with hepatocellular carcinoma (HCC), the most common indication for LLR. Methods: The IC comprise six preoperative factors that allow the grading of operative difficulty as low, intermediate, advanced, or expert. IC scores were validated in patients with HCC who underwent LLR ( n = 77). Results: The median operative time was 212 min (range 57–461 min). The difficulty of the resections was categorized as low in 9% ( n = 7), intermediate in 38% ( n = 29), advanced in 36% ( n = 28), and expert in 15% ( n = 12) of the patients. IC score was significantly linked to operative time, length of stay and liver function ( P < 0.05). The rates of postoperative complications (Clavien–Dindo >II) for low, intermediate, advanced and expert were 0% ( n = 0), 10% ( n = 3), 3.5% ( n = 1) and 50% ( n = 6), respectively ( P = 0.04). Conclusion: The IC can be used to preoperatively assess difficulty of LLR and to predict postoperative complications in HCC patients. Thus, the IC score may be useful to differentiate easy procedures from difficult procedures and is ideal to build an LLR curriculum for upcoming surgeons. Abstract : Highlight Krenzien and colleagues validated the Iwate criteria proposed by the International Consensus Conference on Laparoscopic Liver Resection. The Iwate criteria can be used to preoperatively assess surgical difficulty of laparoscopic liver resection as the spectrum of difficulty ranges from simple wedge resection to major hepatectomy with or without biliary reconstruction.